2022
DOI: 10.1038/s41598-022-22145-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hospitalized patients with SARS-CoV-2 infection during successive waves of the COVID-19 pandemic in a reference hospital in Spain

Abstract: Since the beginning of the COVID-19 pandemic and until September 2021, Spain suffered five waves of infection, the latter being related to the expansion of the Delta variant and with a high incidence. A vaccination campaign began in December 2020 and by the end of the fifth wave 77.3% of people had been fully vaccinated. Examining the changing dynamics of COVID-19 pandemic and its impact on outcomes among those hospitalized is essential. Our objective was to ascertain any differences in the characteristics and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…in any of the omicron cases of our cohort 16 . Our observations are in concordance with clinical data associating an omicron infection with a milder disease course and low lethality 12,17,18 . Thus, the extent of lung injury is still an important denominator for patients’ prognosis and the clinical course of COVID‐19.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…in any of the omicron cases of our cohort 16 . Our observations are in concordance with clinical data associating an omicron infection with a milder disease course and low lethality 12,17,18 . Thus, the extent of lung injury is still an important denominator for patients’ prognosis and the clinical course of COVID‐19.…”
Section: Discussionsupporting
confidence: 88%
“…16 Our observations are in concordance with clinical data associating an omicron infection with a milder disease course and low lethality. 12,17,18 Thus, the extent of lung injury is still an important denominator for patients' prognosis and the clinical course of COVID-19. However, besides attenuation of viral pathogenicity, vaccination or resolved infection improved the specific immune status of the population, and improvement in disease management may also be an important factor for a better outcome of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study based on electronic health records in the United States found that patients with psychiatric disorders had a higher risk for COVID-19 infection than those without psychiatric disorders (adjusted OR = 7.64 for depression; adjusted OR = 7.34 for schizophrenia) (11). Two other studies in Spain found that 45% of COVID-19 inpatients had history of psychiatric disorders and 37% of COVID-19 inpatients had medical conditions (12,13), supporting the view that psychiatric patients are more prone to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, new and more transmissible variants have appeared, while the success of vaccination campaigns has varied in many countries, and as such, the outcomes are hard to predict a priori [2,3]. Understanding the impact of the strategies on the evolution of the disease is essential if definitive treatments are to be defined on a global scale, while alternative treatments need to be found for patients who do not respond to vaccination [4]. A total of 5 SARS-CoV-2 variants of concern have been identified to date: alpha (B.1.1.…”
Section: Introductionmentioning
confidence: 99%